1993
DOI: 10.2105/ajph.83.10.1418
|View full text |Cite
|
Sign up to set email alerts
|

Partner notification for control of HIV: results after 2 years of a statewide program in Utah.

Abstract: Partner notification identified a group with a high seroprevalence of HIV. It was not successful among populations that may be difficult to reach with other interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…The proportion of index clients who provided information about their partners in this project was lower than that found in previously published reports of PCRS. [15][16][17][18] However, a substantial number of the participating index clients at the Los Angeles site were interviewed three or more months after being diagnosed with HIV; when we excluded these individuals from the analysis, we found that 69% of the remaining index clients at all sites had provided partner information, a proportion that is consistent with previous reports.…”
Section: Discussionsupporting
confidence: 82%
“…The proportion of index clients who provided information about their partners in this project was lower than that found in previously published reports of PCRS. [15][16][17][18] However, a substantial number of the participating index clients at the Los Angeles site were interviewed three or more months after being diagnosed with HIV; when we excluded these individuals from the analysis, we found that 69% of the remaining index clients at all sites had provided partner information, a proportion that is consistent with previous reports.…”
Section: Discussionsupporting
confidence: 82%
“…In two studies that used partner notification, the cost of a new HIV diagnosis was $3,800 (seroprevalence, 15%) in Colorado 22 and $6,400 (seroprevalence, 14%) in Utah. 23 In both of these studies, people with newly diagnosed HIV infection provided the names of sexual or needle-sharing partners to state health department staff, who then offered HIV testing to the partners.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the contacts of the first IDU to be diagnosed with HIV in Australia (Blacker ct al, 1986) found four new cases of infection among six identified contacts, and two new cases were found among the five sexual contacts of another early case in Australia (Cooper et al, 1984). More recently in the United States contract tracing has identified cases of HIV infection in individuals who were unaware that they were infected and, hence, at risk of unknowingly infecting others (Landis et al, 1992;Pavio et al, 1993;Waldron et al, 1995).…”
Section: Is There a Role For Contact Tracing In Preventing Hiv Transmmentioning
confidence: 99%
“…Landis et al, 1992;Pavio et al, 1993;Waldron et al, 1995) may not be applicable in all countries. It may be, for example, that in the absence of a comprehensive public health care system IDUs regard a preparedness to identify one's contacts as one of the costs of receiving health care.…”
Section: Is There a Role For Contact Tracing In Preventing Hiv Transmmentioning
confidence: 99%